Domestic Consumption and Uncertainty of Exchange Rate in a Monetary Union:Evidence from the Euro Area - Okafor, Samuel; Lokossou, Juste (The European Journal of Applied Economics, 2021)
The research seeks to uncover how real consumption reacts to real exchange rate uncertainty in the short and long run for the world’s largest monetary union- the Eurozone. Twelve eurozone countries were sampled covering the period 1995Q1-2019Q4. Using generalized autoregressive conditional heteroskedasticity (GARCH) and pooled mean group (PMG), the result shows that exchange rate uncertainty significantly dampens long-run consumption while the short-run effect is mixed. In the benchmark model, a negative and significant error correction coefficient was obtained which allows to argue that i) there is evidence of a return to the long-run equilibrium path for consumption following short run deviations and ii) the speed of adjustment to equilibrium is low, with a coefficient of 4%. This suggests that, in the eurozone, convergence to long-run equilibrium is slow, as the proportion of disequilibrium corrected in one quarter, following a shock, is about 4%, which implies it would take 17 quarters for one half of the disequilibrium, or deviations from the long-run consumption path, to become corrected.